PARADIGMA DALAM KEBIJAKAN DESENTRALISASI DI INDONESIA: SEBUAH KRITIK TERHADAP DOMINASI PUBLIC ADMINISTRATION SCHOOL - Riwanto Tirtosudarmo (LIPI Press, 2008)
In this article, the underlying approach that has been used to formulate the post-Soeharto's territorial reform that produced decentralization laws and regulations is critically reviewed. The so-called Public Administration School or